Karya Karawitan Kontemporer “Evolusi” - Wirata, I Nyoman Arya Wiranbawa (Pusat Penerbitan LPPMPP ISI Denpasar, 2025)
Modern music is an umbrella term that encompasses a wide range of musical genres that developed from the mid-20th century to the present day. The term is often used to refer to innovative and experimental musical works that differ from traditional classical music. Contemporary music reflects technological developments, social changes, and cultural convergence of the modern world. Contemporary music is not limited to a specific style or form, but it encompasses a variety of creative approaches that challenge and expand musical boundaries. Contemporary composers and musicians often explore new techniques such as the use of electronic instruments, sampling, and digital manipulation. Starting from this, there was a desire to create a contemporary music work based on Balinese gamelan entitled Evolution. The method of creating works applies the method of creating Panca Sthiti Ngawi Sani which consists of the inspiration stage (ngawirasa), the exploration stage (ngawacak), the conception stage (ngaplanning), the execution stage (ngawangun) and the production stage (ngebah). The media revealed that the karawitan music works used were 2 Tungguh Rindik Saih Pitu, 2 Tungguh Pegulingan Pegulingan pemade and non-gamelan instruments, namely 2 coconut shells.